Efektivitas Metode Sam’iyah Wa Syafawiyah Dalam Pengajaran Bahasa Arab - Moh. Zarkani (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2020)
Among the existing Arabic learning methods each has advantages and disadvantages, at first the translation method is considered the most suitable for the ability to read effectively and understand content, then the Direct Method appears as a reaction even though it has existed since the Roman Age, then emerged. The Aural Oral Approach (Sam'iyah Wa Syafawiyah) method which was considered the most effective because it is based on linguistic principles which are expected to be able to answer and overcome various problems in the Arabic teaching and learning process whose main goal is that students have good Arabic language skills or proficiency. and right.With the implementation of the Sam'iyah wa Syafawiyah method at Madrasah Tsanawiyah Putra Al-Ishlahuddiny Kediri, West Lombok, it is intended that the mastery of the four language skills is balanced, the language skills in question are: Listening skills, speaking skills, reading skills and writing skills.The approach used in this study is a qualitative approach. The author chooses this qualitative approach in order to obtain broader and more in-depth information about the matters that are the subject of discussion for which answers must be found in this study.implementation of the Sam'iyah wa Syafawiyah method in teaching Arabic in Class II MTs. Putra Al-Ishlahuddiny Kediri based on the theory of the Sam'iyah wa Syafawiyah (Audio Lingual) method which has been described in a literature review, it can be said that it is in accordance with the provisions taught by the theory of the Sam'iyah wa Syafawiyah method although it still needs improvement, while for knowing its success still needs evaluation.Implementation of the Sam'iyah wa Syafawiyah Method in teaching Arabic in class II MTs. Putra Al-Ishlahuddiny Kediri has been running smoothly and in accordance with what is stated in the theory of the Sam'iyah wa Syafawiyah Method, although it still needs improvement because there are several obstacles.